Arsenic removal from drinking water using activated red mud - Christian Tjell, Jens; McConchie, David (Malaysian Journal of Science, 2004)
Red mud is the by-product of alumina production, and in this study seawater-neutralised and activated red mud (called activated Bauxsol, AB) is used as an unconventional novel adsorbent for removing arsenic from water. The adsorption of arsenic onto AB is studied and the pH dependence of the process is investigated for both As(V) (arsenate) and As(III) (arsenite). It is found that the arsenic adsorption follows the Langmuir isotherm, and that the optimal pH for adsorption is 4.5 for arsenate and 8.5 for arsenite with roughly 100% and 53% removals, respectively. The linearized form of Langmuir isotherm is used to calculate the adsorption capacities at pH 7, and found as 39.8 for arsenate and 7.2 p,mol g4 for arsenite. The combined effects of competing anions i.e.. phosphate, silicate, sulphate, and bicarbonate are also tested, and it is found that phosphate and silicate hinder arsenic removal more strongly in the presence of sulphate and bicarbonate, despite the fact that neither sulphate nor bicarbonate are strong suppressers at the concentrations found in natural waters. Consequently, this paper shows that AB can be a very efficient unconventional adsorbent for removing arsenate from water at near neutral pH values in the absence of competing anions, but in their presence of these anions sorptive capacity of AB decreases and therefore either the AB dosages must be increased or the pH values should be adjusted for favourable arsenate removal.